The spiritual way to desistance? Recidivism among former participants in religiously based retreat activities in Swedish prisons - Alm, Susanne; Al Weswasi, Enes; Roxell, Lena (Nordisk Tidsskrift for Kriminalvidenskab, 2024)
Abstract In the years 2001-2019, the Swedish Prison and Probation Service operated religious retreat activities at the high-security prison in Kumla, to which prisoners serving long-term sentences could apply. While the activities were not specifically implemented to reduce recidivism, a process evaluation conducted in 2014-2016 showed that the participants expressed great hope that these experiences would help them desist from crime. The current study examines actual rates of desistance and recidivism among former participants in the religious activities. The study uses data from the Swedish Prison and Probation Service covering inmates released between 2013 and 2019. Propensity score matching is applied. Prior to matching, former inmates who participated in the religious activities were considerably less likely to be reconvicted within three years of release (37 percent) compared to those who did not participate (59 percent). After matching, however, while estimates were still indicative of a recidivistic effect, they no longer reached statistical significance. One interpretation is that given, e.g., their age and type of sentence, the participants already had such a low risk of recidivism as to make further reduction difficult to achieve. Under åren 2001-2019 bedrev Kriminalvården i Sverige en kristen retreatverksamhet på anstalten Kumla, dit långtidsdömda fångar kunde söka sig. Det övergripande syftet med aktiviteterna var inte att minska återfall. En tidigare processutvärdering har dock visat att deltagarna var hoppfulla att deras erfarenheter från retreaterna skulle hjälpa dem att minska återfallsrisken. Syftet med den här studien är därför att analysera upphörande av brott och återfall för tidigare deltagare i klosterverksamheten. I studien används svenska kriminalvårdsdata för alla intagna under åren 2013-2019. Analysmetoden som nyttjas är Propensity score matching. Innan matchning visar resultatet att det var mindre vanligt att de som hade deltagit i retreatverksamheten återföll (37 procent) i jämförelse med de som inte hade deltagit (59 procent). Efter matchning gick resultatet i samma riktning, dock kunde inga signifikanta skillnader konstateras mellan grupperna. En tolkning är att deltagarna i klosterverksamheten, på grund av t ex ålder och typ av straff, redan har en låg risk för återfall, vilket gör det svårt att uppnå signifikanta skillnader.